1985
DOI: 10.1037/0021-9010.70.1.56
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of ratee race effects in performance ratings.

Abstract: A recent review of ratee race effects on performance ratings (Landy & Farr, 1980) found conflicting results. For the present research, meta-analytic techniques were used for more substantive conclusions about the existence of ratee race effects and whether the effects were related to rater race or were moderated by situational factors. The five moderators examined included the study setting (laboratory/ field), rater training (offered/not offered), type of rating (behavior/trait), rating purpose (administrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
259
9
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 328 publications
(293 citation statements)
references
References 58 publications
24
259
9
1
Order By: Relevance
“…One explanation for the relationship between team ethnic diversity and consensus in trust in leaders is that diversity may influence the nature of the dyadic relationship and exchanges between the leader and members. For example, research has shown a positive relationship between rater-ratee racial similarity and performance ratings (Kraiger & Ford, 1985).…”
Section: Hypotheses Resultsmentioning
confidence: 99%
“…One explanation for the relationship between team ethnic diversity and consensus in trust in leaders is that diversity may influence the nature of the dyadic relationship and exchanges between the leader and members. For example, research has shown a positive relationship between rater-ratee racial similarity and performance ratings (Kraiger & Ford, 1985).…”
Section: Hypotheses Resultsmentioning
confidence: 99%
“…More recently, research on relational demography has distinguished between perceived similarity and actual demographic similarity, showing how the tendency for demographically different individuals to receive less favorable evaluations and to become socially marginalized from group decision making is reduced when alternative bases for similarity are made salient (e.g., Pulakos and Wexley, 1983;Kraiger and Ford, 1985;Turban and Jones, 1988). Similarly, while demographic differences between group members can provide a basis for out-group biases in the group, such biases may be avoided when other attitudes, beliefs, or social features that group members have in common are made salient (Kramer, 1991;Huo et al, 1996;Erb et al, 1998).…”
Section: Demography and Influencementioning
confidence: 99%
“…Authors found no support for the race effect. Yet, Kraiger and Ford's (1985) meta-analysis research indicates a significant rate race effect in performance ratings: higher performance scores were given to people of raters' own race. Meanwhile, empirical work on cross-country/culture collaboration (e.g., Binder, 2007;Xie, Song, & Stringfellow, 1998;Zagorsek, Jaklic & Stough, 2004) has also compared participants of different countries based on cultural dimensions such as power distance, uncertainty avoidance, individualism and collectivism, long term orientation, and more as per Hofstede (2001).…”
Section: Driver-passengermentioning
confidence: 99%